PENGARUH PENAMBAHAN ASAM SUKSINAT DALAM MENGHAMBAT KOROSI BAJA DALAM LARUTAN ASAM SULFAT - Gusti, Diah Riski; Aritonang, Henry F.; Azis, Sriwati (CHEMISTRY PROGRESS, 2008)
The objectives of this research were study the effect of addition succinic acid on inhibiting of stainless steel corrosion in sulfuric acid solution. The stainless steel sample sieved and macerated in sulfuric acid solution with concentration of 0.01; 0.02; 0.03; 0.04 and 0.05 M for 24, 48 and 72 hours. The corrosion rate and inhibitor efficiency were evaluated with Asdim and Widharto method. The result showed that corrosion rate of with different concentration higher with increasing of concentration of sulfuric acid. The corrosion rate of stainless steel was higher of 0.3716 mg/cm2 hours at concentration of 0.05 M. However, the addition of succinic acid with different concentration of 1 x 10-3; 2 x 10-3; 4 x ; 4 x 10-3 ; 5 x 10-3 M, relative corrosion rate gave lower. The inhibitor efficiency in succinic acid was 60.60% at concentration 5 x 10-3 for 24 hours. It is concluded that succinic acid having inhibition effect on stainless steel corrosion.